The effect of some soil conditioners and moisture deficiency on the weighted mean diameter and growth of maize (Zea mays L.) cultivated in desert soils. - Murtadha Haleem Shaet; Nihad Shakir Sultan Al-Wally (University of Thi-Qar Journal of agricultural research, 2023)
The experiment was conducted at the Tomato Development Research Station, located in Al-Zubayr district, Basra Governorate, with a sandy loam texture, during the autumn season of August 21, 2022. The objective of the study was to determine the effect of soil conditioners (zeolite at 2% and perlite at 1%, 2%, and 3%) with or without organic matter mixing, as well as the organic matter treatment at 3% and the control treatment, and the soil irrigation level on weighted mean diameter and growth of yellow corn (Zea Mays L.). The experiment was carried out in a randomized complete block design (RCBD) with three replications, and the means were compared using the least significant difference (LSD) test at a 5% probability level. The experiment included 10 treatments for conditioner and two irrigation levels (100% and 75%). The desired characteristics were studied at two depths: 0-15 cm and 15-30 cm at the beginning and end of the season. The results showed that the treatment ZO outperformed all other treatments in weighted mean diameter, recording 5.243 mm at the beginning of the season. However, at the end of the season, treatments ZO, B1O, B2O, B2, B3O, and B3 surpassed the other treatments. The irrigation level of 75% EP exhibited a significant increase of 11.45% in weighted mean diameter at the beginning of the season compared to the 100% EP irrigation level. However, at the end of the season, the 100% EP irrigation level showed a significant improvement in weighted mean diameter. Furthermore, at the beginning of the season, the 15-30 cm depth showed a significant increase in weighted mean diameter compared to the 0-15 cm depth, while there was no significant difference between the two depths at the end of the season. Treatment B3O showed a significant increase in plant height, recording 185.95 cm. Treatments B3O, B3, B2O, and ZO exhibited significant increases in plant dry weight compared to all other treatments, with values of 10,966.67, 10,866.67, 10,633.33, and 10,233.33 kg/ha, respectively.